Lung Function Assessment by Impulse Oscillometry in Adults - Porojan-Suppini N (Dove Medical Press, 2020)
Noemi Porojan-Suppini, Ovidiu Fira-Mladinescu, Monica Marc, Emanuela Tudorache, Cristian Oancea Department of Pulmonology, Center for Research and Innovation in Personalized Medicine of Respiratory Diseases, University of Medicine and Pharmacy “Victor Babeș”, Timișoara, RomaniaCorrespondence: Ovidiu Fira-MladinescuDepartment of Pulmonology, University of Medicine and Pharmacy “Victor Babeș”, Str. Gheorghe Adam nr. 13, Timișoara 300310, RomaniaTel +40 745608856Email mladinescu@umft.roAbstract: Over the past decades, impulse oscillometry (IOS) has gained ground in the battery of pulmonary function tests. Performing the test requires minimal cooperation of the patient; therefore, it is a useful tool, especially in evaluating lung mechanics in children, elderly patients, and those who cannot perform spirometry. Oscillometry has also been used in both clinical and research departments. Studies were published mainly in asthma regarding detection of bronchodilator response and the therapeutic response to different drugs. Furthermore, it has been shown to be a sensitive technique to evaluate disease control. Other studied diseases were COPD, interstitial lung diseases, small airway disease, impairment of lung function due to exposure to occupational hazards or smoking, central airways obstruction, cystic fibrosis, monitoring lung mechanics during mechanical ventilation and sleep, neuromuscular diseases, lung transplant, and graft function. The aim of this review is to present the utility of oscillometry on the previously mentioned clinical fields.Keywords: oscillometry, pulmonary function tests, respiratory resistance, respiratory impedance